Pengaruh Pengembangan Karir dan Motivasi terhadap Kinerja Karyawan pada Perusahaan Air Minum Tirta Mangkaluku Kota Palopo - Sukri Sukri; Indah Pratiwi (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2022)
This study aimed to analyze the effect of career development and motivation on employee performance at the drinking water company Tirta Mangkaluku, Palopo City. This research was a descriptive quantitative research. The sampling technique was carried out by the slovin method. The sample in this study was 61 respondents. The data used in this study was primary data collected through questionnaire survey and google form. Data analysis used multiple linear regression. The results of the study show that 1) Career development has positive and significant effect on employee performance at the drinking water company Tirta Mangkuluku Palopo City. 2) Motivation has positive and significant effect on employee performance at the drinking water company Tirta Mangkuluku in Palopo City.